MENINGKATKAN KONSEP DIRI POSITIF DALAM BELAJAR DENGAN MENGGUNAKAN TEKNIK ROLE PLAYING - Asti Haryati; Yusmansyah Yusmansyah; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of the research was to know the increasing of positive self-concept in learning by using role-playing techniques. The problem of this research was the low of student’s positive self-concept in learning. The problem was